Female delinquents in a birth cohort: Tests of some aspects of control theory - Torstensson, Marie (Journal of quantitative criminology, 1990)
In the light of the rather low, empirical interest in the etiology of female crime and delinquency, this study presents and discusses some findings on aspects of control theory. The data are taken from Project Metropolitan, a longitudinal study of a Stockholm birth cohort comprising 15,117 cases (males and females) studied during a 30-year period. Of the females 791 cases or 11% acquired records of delinquency, drug use, or crime up to age 26. The delinquents were divided according to assumed seriousness and compared to the nondelinquents on two dimensions of the social bond called Attachment to school and Commitment to education. The results show, first, that delinquency varies with the strength of the social bond and, second, that the ability to predict future delinquency with knowledge of these aspects of the bond is limited, as the variance proportions accounted for are low. However, when comparing the explained variances to some well-known studies, we find that the differences are not so extensive.